2023
DOI: 10.1177/08862605231168818
|View full text |Cite
|
Sign up to set email alerts
|

Transition From School Violence Victimization to Reporting Victimized Experiences: A Latent Transition Analysis

Abstract: This study aimed to understand the heterogeneity of school violence experiences among South Korean youth, explicitly examining how each type of violence experienced transitions into different reporting behaviors. A latent profile analysis was conducted to classify different types of violence victimization and reporting behaviors, followed by a latent transition analysis, which contributed to an understanding of the relationships between profiles of violence and reporting. The influence of social support on rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Several investigations have shown that school violence increased significantly after the return to face-to-face classes, compared to the figures reported during COVID-19 confinement [1][2][3]. In Chile, the last report of the Superintendence of Education (SUPEREDUC) regarding complaints in the area of school coexistence reached 1586 cases, where 40% refer to the mistreatment of students, 17% to disciplinary measures, 14% to discrimination and 4% to participation in school activities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have shown that school violence increased significantly after the return to face-to-face classes, compared to the figures reported during COVID-19 confinement [1][2][3]. In Chile, the last report of the Superintendence of Education (SUPEREDUC) regarding complaints in the area of school coexistence reached 1586 cases, where 40% refer to the mistreatment of students, 17% to disciplinary measures, 14% to discrimination and 4% to participation in school activities [4].…”
Section: Introductionmentioning
confidence: 99%